Peran Kepemimpinan Informal Tokoh Bâjing dalam Penguatan Pembelajaran Pendidikan Agama Islam di Madura - Ahmad Said; Faridah Ulvi Naimah (Ahdāf: Jurnal Pendidikan Agama Islam, 2026)
This study is motivated by the limited attention given to the role of informal non-religious actors in strengthening Islamic Religious Education, as existing studies have predominantly focused on formal actors. This research aims to analyse the role of informal leadership of bâjing figures in strengthening Islamic Religious Education learning practices in Madura. This study employs a qualitative approach with a case study design conducted in Ketapang District, Sampang Regency. Data were collected through observation, in-depth interviews, and documentation involving 14 informants selected through purposive and snowball sampling techniques, and were analysed using thematic analysis. The findings reveal that bâjing figures play multiple roles as mediators, social control agents, donors, and promoters of community participation in Islamic education. These roles contribute to improving students’ learning motivation, discipline, and the creation of a more conducive learning environment. The study concludes that informal leadership based on social capital plays a strategic role in strengthening Islamic Religious Education learning practices. Therefore, the development of Islamic Religious Education is not solely dependent on formal actors but also on informal actors who possess strong social legitimacy within the community.